Public expectations concerning confidentiality protection of adolescents' sexual and reproductive health care in Lithuania: Findings of the surveys conducted in 2005 and 2012. (April 2014) - Jaruseviciene, Lina; Zaborskis, Apolinaras; Lazarus, Jeffrey Victor
Abstract Objective An adolescent's right to confidential healthcare is protected by international law and professional consensus. However, parental and social support for confidential sexual and reproductive health (SRH) services, in particular, varies greatly. This study documents Lithuanian residents' expectations with regard to confidentiality protection for adolescents in this domain, and explores the factors related to the diversity of these expectations. Methods Two national surveys of Lithuanian residents completed in 2005 and 2012 using anonymous questionnaires. Participants rated their expectations for confidentiality using a five-point Likert scale for eight types of SRH consultations. Results Public anticipation for confidentiality depended on whether issues related to sexual behaviour or to its consequences were addressed during adolescent consultation. Only younger respondents had higher expectations for confidentiality in both contexts. Public expectations regarding confidentiality were less demanding in 2012 than in 2005. Conclusions The expectation of confidentiality protection was greater for topics related to sexual behaviour than for the consequences of sexual behaviour, such as pregnancy, abortion or a sexually transmitted infection. This implies a need for targeted information strategies for the general population and explicit guidance for physicians on when and for whom care should remain confidential.